Investigations of thermal plasma with metal impurities. Part І: The influence of electrodes composition on plasma properties - Veklich, A.N.; Lebid, A.V.; Soroka, P.V.; Boretskij, V.F.; Babich, I.L. (Вопросы атомной науки и техники, 2012)
Present paper deals with spectroscopic investigations of electric arc discharge plasma in argon flow between Cu- Mo and Cu-Mo-LaB₆ composite electrodes. Obtained profiles of temperature and electron density were used for calculation of plasma composition and metals’ content in assumption of local thermodynamic equilibrium (LTE). Significant influence of LaB₆ admixture on plasma properties was found. Pабота посвящена спектроскопическим исследованиям плазмы электродугового разряда между Cu-Mo и Cu-Mo-LaB₆ композитными электродами в потоке аргона. Полученные распределения температуры и электронной концентрации использованы для расчета состава плазмы и содержания металлов в предположении состояния локального термодинамического равновесия. Установлено существенное влияние примеси LaB₆ на свойства плазмы. Pобота присвячена спектроскопічним дослідженням плазми електродугового розряду між композитними Cu-Mo та Cu-Mo-LaB₆ композитними електродами в потоці аргону. Отримані розподіли температури та електронної концентрації використано для розрахунку складу плазми та вмісту металів у припущенні стану локальної термодинамічної рівноваги. Встановлено суттєвий вплив домішки LaB₆ на властивості плазми.